Influence of different luting protocols on shear bond strength of computer aided design/computer aided manufacturing resin nanoceramic material to dentin - Claudio Poggio; Marco Pigozzo; Matteo Ceci; Andrea Scribante; Riccardo Beltrami; Marco Chiesa (Wolters Kluwer Medknow Publications, 2016)
Background: The purpose of this study was to evaluate the influence of three different luting protocols on shear bond strength of computer aided design/computer aided manufacturing (CAD/CAM) resin nanoceramic (RNC) material to dentin. Materials and Methods: In this in vitro study, 30 disks were milled from RNC blocks (Lava Ultimate/3M ESPE) with CAD/CAM technology. The disks were subsequently cemented to the exposed dentin of 30 recently extracted bovine permanent mandibular incisors. The specimens were randomly assigned into 3 groups of 10 teeth each. In Group 1, disks were cemented using a total-etch protocol (Scotchbond™ Universal Etchant phosphoric acid + Scotchbond Universal Adhesive + RelyX™ Ultimate conventional resin cement); in Group 2, disks were cemented using a self-etch protocol (Scotchbond Universal Adhesive + RelyX™ Ultimate conventional resin cement); in Group 3, disks were cemented using a self-adhesive protocol (RelyX™ Unicem 2 Automix self-adhesive resin cement). All cemented specimens were placed in a universal testing machine (Instron Universal Testing Machine 3343) and submitted to a shear bond strength test to check the strength of adhesion between the two substrates, dentin, and RNC disks. Specimens were stressed at a crosshead speed of 1 mm/min. Data were analyzed with analysis of variance and post-hoc Tukey's test at a level of significance of 0.05. Results: Post-hoc Tukey testing showed that the highest shear strength values (P < 0.001) were reported in Group 2. The lowest data (P < 0.001) were recorded in Group 3. Conclusion: Within the limitations of this in vitro study, conventional resin cements (coupled with etch and rinse or self-etch adhesives) showed better shear strength values compared to self-adhesive resin cements. Furthermore, conventional resin cements used together with a self-etch adhesive reported the highest values of adhesion.